2022
DOI: 10.1002/kjm2.12590
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblast‐secreted miR‐421 promotes pancreatic cancer by regulating the SIRT3/H3K9Ac/HIF‐1α axis

Abstract: This study was designed to explore the effects of exosomal miR‐421 secreted by cancer‐associated fibroblasts (CAFs) on pancreatic cancer (PC) progression and the mechanisms involved. CAFs and exosomes (exos) were isolated and identified. PC cells were treated with CAF‐derived exos (CAF‐exos). Western blotting and quantitative polymerase chain reaction (qPCR) were used to measure miR‐421, sirtuin‐3 (SIRT3), and hypoxia duciblefactors‐1 alpha (HIF‐1α) levels. Cell counting kit‐8 (CCK‐8), wound‐healing, and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The current study identified the reduced expression of ENTPD3-AS1 in LUAD patients, who have poor clinical outcomes, supporting that ENTPD3-AS1 could act as a promising prognostic predictor in LUAD. miR-421, which is an oncomir associated with various cancers, including pancreatic cancer, cholangiocarcinoma, and LUAD [22][23][24], is sponged by ENTPD3-AS1. Indeed, the knockdown of ENTPD3-AS1 or miR-421 inhibitors decreased cell proliferation, enhanced cell migration and epithelial phenotype transition in A549 cells, supporting the findings that ENTPD3-AS1 inhibited the oncogenic function of miR-421 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…The current study identified the reduced expression of ENTPD3-AS1 in LUAD patients, who have poor clinical outcomes, supporting that ENTPD3-AS1 could act as a promising prognostic predictor in LUAD. miR-421, which is an oncomir associated with various cancers, including pancreatic cancer, cholangiocarcinoma, and LUAD [22][23][24], is sponged by ENTPD3-AS1. Indeed, the knockdown of ENTPD3-AS1 or miR-421 inhibitors decreased cell proliferation, enhanced cell migration and epithelial phenotype transition in A549 cells, supporting the findings that ENTPD3-AS1 inhibited the oncogenic function of miR-421 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…In HCC, miR-20a-5p has been demonstrated to have a comparable impact ( Qi et al, 2022 ). Other studies about CAF-derived exosomal miRNAs’ role in invasion and migration are shown in Table 1 ( Xu et al, 2019 ; Yang F. et al, 2020 ; Guo et al, 2020 ; Shi et al, 2020 ; Liu et al, 2021 ; Zhou et al, 2022 ; Wu et al, 2023 ).…”
Section: Function Of Caf-derived Exosomal Mirna In Promoting Tumorige...mentioning
confidence: 99%
“…Studies have revealed that the miRNAs, proteins, and other biomarkers within exosomes derived from CAFs can influence crucial biological processes in pancreatic cancer cells [ 8 10 ]. The exosomes in the pancreatic tumor microenvironment contain RNA molecules, including but not limited to miR-10a-5p [ 11 ], miR-21 [ 12 ], miR-22 [ 8 ], miR-106b [ 13 ], miR-125b [ 8 ], miR-331-3p [ 14 ], miR-421 [ 15 ], miR616-3p [ 16 ], miR-1246 [ 17 ], miR-1290 [ 17 ], miR-3173-5p (Acyl-CoA Synthetase long chain family member 4 (ACSL4)-targeting miRNAs) [ 18 ], miR-4456 [ 16 ], miR-5703 [ 19 ], ANXA6/LRP1/TSP1 [ 8 , 20 ], Hyaluronic Acid (HA) [ 21 ], tRF-19-PNR8YPJZ [ 22 ], as well as long non-coding RNA UCA1 [ 23 ] (Table 1 ). They promote the growth and dissemination of pancreatic cancer cells by modulating signaling pathways in the tumor microenvironment, especially those related to tumor proliferation, cell cycle control, and apoptosis.…”
Section: Relationship Between Cafs-derived Exosomes and Pancreatic Ca...mentioning
confidence: 99%